Visible-Light Photocatalysis of Carbon-Based Materials - Yao, Yunjin (IntechOpen, 2018)
Carbon-based photocatalysis has been considered as an economic, safe, renewable, and clean technology, for various applications. However, the pristine carbon material is usually restricted by unsatisfactory photocatalytic efficiency and practical applications due to the insufficient solar light absorption, the low-surface area, and the fast recombination of photogenerated electron-hole pairs. Various modification strategies, such as elemental and molecular doping, preparation of mesoporous carbon materials, and combination of conductive materials, are adopted to enhance the photocatalytic activity of carbon materials. In this book, we intend to describe the great potential of efficient and low-cost carbon-based materials in various realms, such as photodegradation of organic compounds, water splitting, and selective organic transformations.